Assessment of ionizing radiation from electronics device in some selected viewing centers in Mubi, Adamawa State - Gaya, K. G.; Yaratsada, I. (BOHR Journal of Computational Intelligence and Communication Network, 2025)
Today, the use of television as a tool in the work place, academic institutions, recreation facilities, homes, and sports viewing centers has become very common, it is estimated globally that people spend hours staring into a television monitor. This study aims to carry out an assessment on the ionizing radiation from the selected viewing centers in Mubi with a view to determine the possible safety exposure, absorbed radiation dose, and effective dose equivalent of the ionizing radiation from the television. Measurement was conducted using a radiation counter (Geiger Muller Counter) at a distance of 1, 1.8, 2.6, 3.4, 4.2, and 5.0 m, respectively. The absorbed dose, dose equivalent, and effective dose equivalent of Man-Tunkura, K. B. and T-Kurna sport centers were found to be 0.5741, 0.6964, and 0.6864 mGy; 0.0115, 0.0137, and 0.0139 Sv, and 0.0237, 0.0283, and 0.0287 Sv, respectively. The result obtained was compared with the ICRP standard safety lower limit for radiation protection, which falls far below the standard safety limit recommended. This implies that it is safe for people watching television with respect to the distance mentioned above.